Head to head : - Thurow, Lester (Warner Books, 1993)
A perceptive interpretive appraisal of the coming trilateral struggle for world dominion. Thurow (Dean/MIT-Sloan School of Management; The Zero-Sum Solution, 1985, etc.) takes a contrarian approach in predicting that Europe, not America or Japan, could prove the biggest winner in a bloodless clash that promises to shape the 21st century. At the start of 1995, Thurow notes, the EC will constitute a unified market with a well-educated population of 337 million and a GNP larger than that of the US; the addition of nonmember nations, plus erstwhile Soviet republics and/or satellites, would boost the head count to 850 million. Under German leadership, he insists, the Continent will do and pay whatever is necessary to achieve genuine integration, if only to forestall disruptive immigration flows. In the meantime, Thurow observes, corporate America's individualist, profit-maximizing enterprises are engaged in a spirited competition with the communitarian empire-builders of Japan, and the victor will determine the rules by which the great game of capitalism is played for decades to come. But having reviewed the standing of US business vis-…-vis that of EC and Japanese rivals in eight key industries (aircraft, consumer electronics, machine tools, semiconductor devices, etc.), the author leaves little doubt as to which country is likely to be on the losing side. Thurow closes with a comprehensive agenda designed to renew America's capacity to survive and thrive in the brave new commercial world now in prospect. A thoughtful, thoroughgoing analysis of a consequential conflict among economic superpowers, worthy of a wide readership